A STUDY OF TRAFFIC FLOW ON AUTOROUTE USING MATHEMATICAL MODELLING - et. al, S. Krithika (International Journal of Advanced Science and Technology, 2020)
A study of traffic flow on auto-route using mathematical modeling is the paper like fish without water. We have developed a discrete velocity mathematical model by relating an unchanging conditions for vehicular traffic along a multilane road. The effect of the paper is to investigate the overall interaction of the vehicles along the distance of the road. We also remark, the density of cars per mile modifying the net rate of interaction between them. A mathematical macroscopic traffic flow model i. e, the relationship among traffic flow known as Lighthill Whitham Richards (LWR) model concluded with a closure non-linear velocity-density relationship submit a quasi-linear first order partial differential equation as traffic model. Initial Boundary Value Problem (IBVP) is a finite differences approximate the derivatives.